If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1x(1 + z) = x y + (1 * -1x + z * -1x) = x y + (-1x + -1xz) = x Reorder the terms: -1x + -1xz + y = x Solving -1x + -1xz + y = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1x + -1xz + -1x + y = x + -1x Reorder the terms: -1x + -1x + -1xz + y = x + -1x Combine like terms: -1x + -1x = -2x -2x + -1xz + y = x + -1x Combine like terms: x + -1x = 0 -2x + -1xz + y = 0 Add '-1y' to each side of the equation. -2x + -1xz + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 -2x + -1xz + 0 = 0 + -1y -2x + -1xz = 0 + -1y Remove the zero: -2x + -1xz = -1y Combine like terms: -1y + y = 0 -2x + -1xz + y = 0 The solution to this equation could not be determined.
| .60x=30 | | (x+3)(2x-12)=0 | | p(x)=2x+-1 | | 0=2x^2+8x-960 | | 18=500x-5x^2 | | 11x+y=-27 | | -4x+6=0-5x | | 8n=51+3 | | 3x+10=-22-5 | | 270=(13+2x)x(9+2x) | | 3w^2-365x+8550=0 | | (5y+p)+10y=0 | | 5x+2=4x+24 | | (6P+3)= | | 20x+2=20x+2 | | 8n=51-3 | | 9x-(7x-7)=21 | | 4x+2=4x+22 | | N=yp | | 8(x^2-x+8)=0 | | (3x^2-4x+17)+(7x^2+7x-75)= | | 4+2p=6p-20 | | 75x+35x-10=0 | | 5p+6-2p-4=17 | | 0.0001x+2=4x+2 | | 7(x-4)-4x=2x-3-(5-6x) | | 1234x+2=4x-99 | | 4(x-5)=(5-x)4 | | (2v)-4=8 | | 2c-16=10c | | 24x+2=4x+-8 | | b^2=8b-22 |